ANALYSIS OF STUDENTS’ MASTERY TO USE PREPOSITIONS AT THE INFORMATION TECHNOLOGY STUDENTS OF STATE POLYTECHNIC OF CILACAP - Eka Dyah Sari (Politeknik Negeri Bengkalis, 2019)
Communication skill in English is regarded important nowadays. People need to have good English communication skill to express their feelings better. Some Indonesian students find it quite difficult to communicate well in English. One of the aspects that needs to master well is vocabulary aspect. Vocabulary does not consist of vocabulary only, but it also includes parts of speech, such as verbs, nouns, pronouns, adjectives, adverbs, conjunctions, and prepositions. Preposition as one of the parts of speech plays significant role in communication, but some Indonesian students face some difficulties in applying it. The subject consisted of 22 students of Information Technology study program. This study is a case study in nature by using combination of quantitative and qualitative approaches in analysis. In analyzing the data, some steps were used. First, the writer analyzed the correct answers of the students and categorized them into the suitable profile. And the last, the writer analyzed the problems faced by the students of using prepositions. The result of the study showed that most of the Information Technology students (63,64%) achieved satisfactory grade in using prepositions. The average percentage of the students’ correct answer was 75,64% in which it showed that the students were on the average achievement in using prepositions. It could also be concluded that some students still found difficulties in applying the correct prepositions because they did not clearly understand the difference among the prepositions. More practice is regarded necessary to make the students’ mastery to use prepositions better.